In situ x-ray diffraction analysis of 2D crack patterning in thin films. (15th February 2019) - Faurie, D.; Zighem, F.; Godard, P.; Parry, G.; Sadat, T.; Thiaudière, D.; Renault, P.-O.
Abstract: In this work, the effect of the loading path on the multicracking of Nickel thin films on Kapton® substrate was studied thanks to an experimental set-up combining controlled biaxial deformation, x-ray diffraction and digital image correlation. Samples were biaxially stretched up to 10% strain following either a single equibiaxial path or a complex one consisting of loading successively along each of the axes of the cruciform specimen. While the first path leads to a mud-crack pattern (random), the second leads to a roman-bricks one (square). Moreover, the in situ x-ray diffraction experiments show that the stress field developed in the thin film during the multicracking is clearly dependent on the loading path. By combining the study of stresses and x-ray diffraction peaks linewidth, we evidenced mechanical domains related to initiation of cracks and their multiplication for each loading path. Moreover, stress evolution in the thin film during mud-crack pattern formation is significantly smoother than in the case of roman-bricks one as represented in the plane stress space. Graphical abstract: Image 1